(untitled) (Global Journal of Science Frontier Research, 1969)
Çatalca, located on the ridge between the Marmara and the Black Sea, is a rural district of Istanbul having the temperate climate. Landuse involves farming and forestry. This study makes a contribution and revises the applicability of two medium spatial resolution satellite sensors, NOAA AVHRR NDVI and MODIS (Terra) NDVI, for prediction to potential forest resource management in Çatalca district of Turkey on various spatial scales. The NOAA AVHRR NDVI sensor was chosen in view of its unique value for long-term climate impact studies. The MODIS (Terra) sensor, as a newer generation sensor specifically designed for, inter alia, terrestrial applications, since it provides the opportunity for observations at higher spatial and spectral resolution compared to NOAA AVHRR (NDVI). The required data preparation for the integration of MODIS data into GIS is described with a focus on the projection from the MODIS/Sinusoidal projection to the national coordinate systems. However, its low spatial resolution has been an impediment to researchers pursuing more accurate classification results. This paper summarizes a set of remote sensing applications of NOAA AVHRR NDVI/MODIS (Terra) NDVI datasets in estimation and monitoring of seasonal and inter annual ecosystem dynamics which were designed for forest resource management and can be implemented over Turkey.